Factors Affecting Waste Management in Ibadan North West Local Government - Adetoro, Adeoye Buzrat; Oboh, Joy Isioma; Philip, Zorto Dwamo; Fagbamigbe, Adenike O; Adeniyi JP , Balogun Francis; Adijat, Ogundare Atinuke (American Journal of Biology and Natural Sciences, 2024)
Introduction Solid Waste Management (SWM) is a critical issue affecting public health and environmental sustainability, exacerbated by rapid urbanization and increasing waste generation. Historically, solid waste management has evolved from ancient practices to contemporary systems grappling with modern challenges. The rise in urban populations has intensified the strain on municipal waste systems, especially in developing countries like Nigeria. In Ibadan North West Local Government Area (LGA), waste management practices face significant obstacles including inadequate infrastructure and economic constraints, impacting both the environment and public health. Objective This study aims to analyze the factors affecting waste management in Ibadan North West LGA, assess their impact on public health, and provide recommendations for improving solid waste management practices. The research seeks to understand the current waste management practices, identify key challenges, and propose strategies to enhance waste management in this region. Method of Analysis A descriptive cross-sectional study was conducted using a self-designed questionnaire to gather data on waste disposal practices within Ibadan North West LGA. A multi-stage sampling technique was employed to select participants. The collected data was coded, entered, and analyzed using Statistical Package for Social Sciences (SPSS) version 20. Descriptive statistics, including tables and frequencies, were used alongside inferential statistics, with Chi-square tests employed to explore the relationship between variables. Results The study population had a mean age of 27 years, with 56.5% female and 43.5% male respondents. Educational attainment varied: 57.6% had secondary education, 20.6% had no formal education, 9.4% had basic education, and 12.5% had tertiary education. The majority (81.8%) lived in households of 4-6 members. Occupations included 47.1% traders, 27.9% civil servants, and 25.0% self-employed individuals. Respondents largely believed that improper waste management increases disease risk (87.0%), contaminates water sources (91.4%), causes air pollution (87.2%), and fosters pests (85.2%). Awareness of educational programs related to waste management was high (97.4%), with 75.8% seeking information daily. Food waste was the most common type generated (67.9%), and 71.6% reported daily waste generation. Most households (52.1%) used closed containers for waste storage, with challenges including high disposal costs (40.4%), lack of disposal sites (16.4%), and collection delays (26.0%). The majority (71.1%) had a dumping site nearby, with 67.7% located within 10-50 meters. Management methods included burying (69.3%), burning (20.6%), and unattended sites (10.2%). Barriers to effective waste management included inadequate infrastructure (87.8%), insufficient policies (74.7%), lack of community awareness (85.7%), and socioeconomic factors (84.9%). Conclusion The study highlights significant issues in waste management practices in Ibadan North West LGA, including high disposal costs, inadequate infrastructure, and delays in collection. Despite high levels of public awareness, challenges persist, necessitating targeted interventions. Recommendations include investing in waste management infrastructure, strengthening policy enforcement, enhancing public awareness campaigns, and addressing socioeconomic factors. Community engagement and participation are crucial for successful waste management initiatives, aiming to improve environmental and public health outcomes.